MOTHER TONGUE ISSUES AND CHALLENGE IN LEARNING ENGLISH AS FOREIGN LANGUAGE - Lina Septianasari (Sanata Dharma University Yogyakarta, 2019)
Learning English as a foreign language (EFL) is quite challenging for particular learners. Their mother tongue somehow can be such an obstacle in comprehending the language they learn. The interference of their mother tongue more or less influence EFL Learners’ language acquisition. The aims of this research are to find out (1) the interference of learners mother tongue in acquiring English; and (2) the challenge faced by EFL Learners in acquiring English as their foreign language. The population of this sample is EFL learners at University level in Bandung. The researcher used purposive sampling to collect the data. Triangulation is used during the data collection process. Those are observation, test items, and interview. Relevant theories are used to analyze the data. The data shows that the grammatical rule and phonological aspect of learners’ first language affect their language production. The different sound systems in Bahasa Indonesia and English becomes a challenge for EFL learners in their speech production. The interference of mother tongue has been identified both in English vowels and consonants.